Penerapan Teknologi Augmented Reality Pada Produk Kerajinan Rotan Sebagai Media Promosi Berbasis Android - Ma'ruf, Muhammad Anas; Handayani, Irma (Journal of Information System Research (JOSH), 2024)
Sabda Rattan Furniture & Crafts is a furniture shop that sells various rattan and bamboo craft products. The shop operates in the rattan and furniture craft industry. The shop is located at Jl. Ahmad Jazuli No.21, Kotabaru, Kec. Gondokusuman, Yogyakarta City, Yogyakarta Special Region. The development of increasingly sophisticated technology has made competition in the rattan craft business increasingly fierce, especially competition in marketing products. The promotional media used by the Sabda rattan furniture & craft shop still uses paper containing 2-dimensional images of rattan craft products so it is less interactive and interesting. Based on these problems, this research builds a new promotional media using Augmented Reality technology. This technology can display models of rattan craft products in 3 dimensions using Android. MDLC (Multimedia Development Life Cycle) is a method used in software development. The final result of this research is an application that can display rattan craft models in 3 dimensions by scanning markers or without markers with the help of an Android smartphone.